PET/CT Findings in a Case With FDG-Avid Disseminated Lacrimal Gland MALToma With Sequential Development of Large B-Cell Lymphoma and Gastric MALToma. (February 2015) - Yildirim-Poyraz, Nilufer; Ozdemir, Elif; Basturk, Abdulkadir; Kilicarslan, Aydan; Turkolmez, Seyda
Abstract : Abstract: Primary orbital lymphomas are rare; the major histopathologic type is extranodal marginal-zone B-cell lymphoma of mucosa-associated lymphoid tissue (MALT) or MALToma. We present a case of a 79-year-old female patient with FDG-avid lacrimal gland MALToma with nodal and pulmonary involvement (stage IVE). Nasopharynx and gastric involvement were detected on restaging 18 F-FDG PET/CT after rituximab therapy, and it was found to have a site of transformation to diffuse large B-cell lymphoma (DLBCL) in the nasopharynx. Gastric MALT lymphoma was also confirmed histopathologically, and she then underwent combination chemotherapy regimen, resulting in regression after 3 courses.